METHODS OF EVALUATION OF THE FUNCTIONAL STATUS OF THE LIVER IN THE PLANNING OF ANATOMICAL RESECTIONS ABOUT PRIMARY AND METASTATIC TUMORS: CURRENT STATE OF THE PROBLEM, THEIR OWN EXPERIENCE AND PERSPECTIVES - D. V. Sidorov; N. A. Rubtsova; A. V. Leontyev; M. V. Lozhkin; L. O. Petrov; T. N. Lazutina; I. V. Pylova; P. A. Korolev; A. G. Isaeva (Исследования и практика в медицине)
Objective. Background 99mTc-technephyt hepatobiliary scintigraphy (HBS) and 13C-methacetin breath test were used as a quantitative methods to evaluate liver function. The aim of this study was to compare future remnant liver function assessed by 99mTc-technephyt dynamic hepatobiliary scintigraphy with results of methacetin breath test in the prediction of liver failure after major liver resection. Materials and methods. Methacetin breath test and 99mTc-technephyt hepatobiliary scintigraphy were performed prior to major resection in 53 high-risk patients, including 48 patients with hepatic metastases from colorectal cancer and 5 patients with hepatocellular carcinoma . Liver function determined with HBS was compared with methacetin breath test by unified scale.Results.  A strong positive association (r = 0.706) was found between 13C-methacetin breath test determined with 99mTc-technephyt hepatobiliary scintigraphyConclusions.  Preoperative 99mTc-technephyt hepatobiliary scintigraphy with 13C-methacetin breath test are a valuable techniques to estimate the risk of postoperative liver failure.They offers a unique combination of functional liver uptake and excretion with the ability to assess the preoperative liver function reserve and to estimate the remnant liver function preoperatively . This combination might significantly improve preoperative evaluation and postoperative outcomes in liver surgery.